Penyelesaian Sengketa Pajak Di Bidang Pajak Pertambahan Nilai - Erikson Sihotang (Universitas Mahendradatta, 2018)
Implementation of tax audits often occur due to differences ofopinion between the Taxpayer with the Fiskus of payments to be made by thetaxpayer. Application for Appeals is one of the rights granted by taxation regulationto the Taxpayer. In this research, will be examined on the subject of dispute overthe dispute on Value Added Tax, and the process of settling the dispute on ValueAdded Tax on the Tax Court. This research is a normative juridical research usingapproach of legislation and conceptual approach, concerning the settlement of taxdispute. Based on the results of the discussion, that the subject matter of the disputeover the dispute on Value Added Tax is: a. The basic correction of the impositionof value added tax; b. The correction of domestic delivery; c.Correction of deliveryof heavy equipment rental services; d. Correction is not a taxable item, localdelivery occurs; e.Correct positive sales discount; f. Positive correction of customs duties; g. Correction of input tax invoice; h. There is no tax invoice for delivery tothe bonded zone. The process of settling the dispute on Value Added Tax at the TaxCourt starts from the appeals process of tax dispute in accordance with the taxcourt's law of conducting an examination of the appeal letter, then having to gothrough the process of preparation of the trial, then the judges will be investigatedto examine the principal issue of the case, then with the verification of the partiesand ending with the appeal decision.